PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA DAN LOYALITAS KARYAWAN PADA PT SIANTAR TOP, TBK - Supriadi Siagian (SUAN PUBLISHER, 2024)
Leaders have an important role in companies achieving optimal profits with the help of employees. Leadership style is one of the factors that drives employee performance and employee loyalty in the company. This study was conducted to analyze the extent to which leadership style influences Customer Performance and Loyalty at PT Siantar Top, Tbk. The population in this study was 128 employees and this study used a random sampling method in sampling. The sampling method used the slovin formula and the sample taken was 35 people. Data collection was carried out by distributing questionnaires to respondents. The results of the data tabulation will be processed using SPSS version 24. The results of this study indicate that there is a positive and significant influence between leadership style and performance, and has a positive and significant influence between leadership style and employee loyalty